(untitled) (Agroindustria, Sociedad y Ambiente, 2023)
Water is an increasingly limited element, which makes it necessary to consider a strategy for its recycling, especially in urban areas, which will have a positive impact on economic sectors such as agribusiness, therefore, the objective of this research was to make an inventory of sustainable strategies for water recirculation in housing units and their impact on water needs in agribusiness. For this purpose, an analysis of the statistical information on water demand and deficit in Latin America and Colombia was carried out, followed by a systematic exploration in databases and high impact search engines such as Scopus, Latindex, Scielo, Researchgate and Google Scholar; selecting articles describing water recycling strategies and the advantages and disadvantages of using the recirculation technique. The results found indicate that it is a viable and sustainable alternative in housing units, due to its low investment and the quality of the water compared to urban and industrial wastewater treatment systems, allowing maximizing its use and making the resource available for agro-industrial production, guaranteeing food sovereignty and supplying the food needs of the population.